Performance analysis of wireless communication link using orthogonal FDM (OFDM) over faded channel and space time block code - Auyan, Tasfeen (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2010.